Biochemical and gene expression studies reveal the potential of Aspergillus oryzae-fermented broken rice and brewers' rice water extracts as anti-photoageing agents: Rice as functional bioingredients - Jamaluddin, Anisah; Mohd Abd. Rahman, Siti Muneerah; Abd. Manan, Musaalbakri; Abd. Razak, Dang Lelamurni; Abd. Rashid, Nur Yuhasliza; Abd. Ghani, Amsal; Mohd Yusof, Nurul Yuziana (Cellular and Molecular Biology, 2023)
In this study, UVA- and UVB-irradiated human fibroblasts were used to investigate the anti-photoaging efficacy of two aqueous extracts from Aspergillus oryzae-fermented broken rice (FBR) and brewers' rice (FBrR). As UVA and UVB can damage the dermal and epidermal layers, respectively, two UV radiation approaches were utilised: i) direct UVA irradiation on fibroblasts, and ii) UVB-irradiated keratinocytes indirectly co-cultured with fibroblasts to observe their epithelial-mesenchymal interaction during UVB-induced photoaging. The anti-photoaging properties were tested utilising biochemical tests and quantitative polymerase chain reaction (qPCR). The treatment of UV-irradiated human fibroblasts with FBR and FBrR dramatically downregulates MMP-1 and SFE gene expression. Nonetheless, MMP-1 secretion was inhibited by FBR and FBrR, with more substantial decreases in UVB-treated co-cultures, ranging from 0.76- to 1.89-fold relative to the untreated control. In UVA-treated fibroblasts, however, the elastase-inhibiting activity of FBR and FBrR is up to 1.63-fold and 2.13-fold more potent, respectively. In addition, post-UV irradiation treatment with FBR and FBrR was able to repair and enhance collagen formation in UVA-irradiated fibroblasts. Both FBR and FBrR were able to upregulate elastin gene expression in fibroblasts under both culture conditions, especially at 50 µg/mL. The pro-inflammatory cytokines TNF-, IL-1ß, and IL-6 were likewise lowered by FBR and FBrR, which may have contributed to the anti-photoaging effect of the UVB-treated co-culture. These results reveal that FBR and FBrR inhibit photoaging in human fibroblasts under both UV induction conditions. In conclusion, FBR and FBrR may be attractive bio-ingredients for usage in the cosmetic sector as cosmeceuticals.